Optic neuropathy in superficial intracranial siderosis. - Painter, S; Mathew, L; Quaghebeur, G; Esiri, M; Elston, J (2010)
Superficial intracranial siderosis is a degenerative condition secondary to recurrent occult subarachnoid hemorrhage. Progressive sensorineural deafness, cerebellar ataxia, and pyramidal signs are well-documented clinical manifestations, but optic neuropathy is not a recognized feature. We describe 2 patients with clinical and electrophysiological evidence of optic nerve/chiasm dysfunction and MRI signal abnormalities consistent with hemosiderin staining of the anterior visual pathway. In a third case, neuropathological examination of the optic chiasm showed demyelination attributed to hemosiderin deposition. We suggest that anterior visual pathway damage may be underrecognized in this condition.